Interaction and Immediacy in Online Learning - Woods, Robert H.; Baker, Jason D. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
This article presents the concepts of interaction and immediacy and discusses their theoretical frameworks, implications, and relationship with one another. The authors propose the development of a new conceptual model and recommend additional antecedent research.